2019
DOI: 10.5114/ain.2019.85769
|View full text |Cite
|
Sign up to set email alerts
|

Spatial anticipatory attentional bias for alcohol: A preliminary report on reliability and associations with risky drinking

Abstract: Introduction: Although risky drinking and alcohol dependence have been associated with spatial attentional biases, concerns have been raised about the reliability of the frequently-used dot-probe task. A form of anticipatory bias related to predictive cues has been found to be related to alcohol-related processes, and to have high reliability in the context of threat stimuli. It remains to be determined whether this anticipatory attentional bias also has good reliability for alcohol stimuli. Further, correlati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…However, although eyetracking can measure overt attention shifts (responding by directly moving and focussing the gaze on a target), it does not measure covert attention shifts (responding by seeing something peripherally without directly focussing the gaze on a target). Eye-tracking might be a valuable addition to this field of research, but as also encouraged by other researchers [12] a task that can reliably measure the influence of covert attention shifts remains also desirable (see for example attempts to improve the reliability of the visual probe task, [13]).…”
Section: Introductionmentioning
confidence: 99%
“…However, although eyetracking can measure overt attention shifts (responding by directly moving and focussing the gaze on a target), it does not measure covert attention shifts (responding by seeing something peripherally without directly focussing the gaze on a target). Eye-tracking might be a valuable addition to this field of research, but as also encouraged by other researchers [12] a task that can reliably measure the influence of covert attention shifts remains also desirable (see for example attempts to improve the reliability of the visual probe task, [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, performance is not dependent on a given trial's specific exemplars, but on the predicted categories of stimuli that could have been presented. Possibly partly due to this removal of a source of variability, the cVPT has been found to have relatively good reliability (Gladwin, 2018;Gladwin, Möbius, Mcloughlin, & Tyndall, 2018). A theoretical question is what is causing the bias.…”
mentioning
confidence: 99%
“…The authors also demonstrated that an index of the difference in mean response latencies for probes presented in each stimulus location, providing a measure of the degree to which attention was biased, held greater levels of split-half internal reliability ( r = .56 to .69). While this particular paradigm has not shown a link with anxiety vulnerability, it has revealed relationships between biased attention to cues signalling alcoholic beverages and individual differences in alcohol consumption behaviour (Gladwin, 2019 ; Gladwin et al, 2020 ). Other studies have used the cue-signal approach while manipulating the probability of the target location relative to cue locations to experimentally induce an attentional bias towards or away from cues signalling negative information (Gladwin et al, 2021 ).…”
mentioning
confidence: 99%